2009
DOI: 10.1002/jcb.22088
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of distinct clonal populations of bone marrow mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSCs) have attracted immense research interest in the field of regenerative medicine due to their ability to be cultured for successive passages and multi-lineage differentiation. The molecular mechanisms governing MSC self-renewal and differentiation remain largely unknown. The development of sophisticated techniques, in particular clinical proteomics, has enabled researchers in various fields to identify and characterize cell specific biomarkers for therapeutic purposes. This study se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…Studies on the differentiation potential of the several BM-MSC subpopulations have also been carried on by Satomura et al [42], that showed that not all the stem cells subpopulations that were isolated from the bone marrow were able to differentiate into osteoblasts. Other studies suggested the presence of specific subpopulations in the bone marrow that have higher ability for the differentiation into the lipogenic lineage while other subpopulations present a superior ability for the osteogenic differentiation [37][38][39][43][44][45][46]. These studies clearly demonstrate the presence of subpopulations in the BM-MSC and highlight the importance of developing isolation methods that allow obtaining selected cells populations and studing the characteristics that differ among them.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Studies on the differentiation potential of the several BM-MSC subpopulations have also been carried on by Satomura et al [42], that showed that not all the stem cells subpopulations that were isolated from the bone marrow were able to differentiate into osteoblasts. Other studies suggested the presence of specific subpopulations in the bone marrow that have higher ability for the differentiation into the lipogenic lineage while other subpopulations present a superior ability for the osteogenic differentiation [37][38][39][43][44][45][46]. These studies clearly demonstrate the presence of subpopulations in the BM-MSC and highlight the importance of developing isolation methods that allow obtaining selected cells populations and studing the characteristics that differ among them.…”
Section: Introductionmentioning
confidence: 91%
“…The principle of this isolation method is the property of the ASCs to adhere to the surface of the culture flasks/dishes and it obviously results in the presence of other cell types that may compromise the proliferation and/or differentiation potential of ASCs [30,[33][34][35][36]. The use of other methods may allow studying the possible presence of subpopulations, similarly to what has been found in the bone marrow [37][38][39][40]. In fact several BM-MSC subpopulations have been studied in order to establish the phenotype, the gene expression and the proliferation rate as described in a study by Tormin et al [39], which identified at least three different subpopulations; Gronthos et al [41] were able to isolate and purify a STRO + /VCAM1 + BM-MSC subpopulation that exhibited high proliferative properties.…”
Section: Introductionmentioning
confidence: 93%
“…calmodulin), and glycolytic proteins (e.g. glyceraldehyde-3-phosphate dehydrogenase) (Mareddy et al, 2009). Furthermore, surface marker expression across clones suggest that CD200 marks osteogenic subpopulations, while SSEA4 and CD140a are associated with adipogenic capacity (Pontikoglou et al, 2016;Rostovskaya and Anastassiadis, 2012).…”
Section: Inter-clonal Molecular Variationmentioning
confidence: 99%
“…While all of the aforementioned studies were performed on morphologically and functionally heterogeneous (bulk-cultured) bone marrowderived MSCs, studies comparing the proteomic profi les of fast-growing clonal bone marrowderived MSC populations with tri-potential differentiation capacity to slow-growing clones with uni-potential differentiation capacity have been performed in order to more effectively explore the mechanisms governing stem cell self-renewal and differentiation (Mareddy et al 2009 ) . Of note, higher expression of calcium-and actinbinding proteins such as calmodulin and tropomyosin alpha-4 chain was observed in the fast-growing stem cell clones while higher expression of caldesmon, annexin A1 and progerin was seen in slow-growing non-stem cell clones.…”
Section: Bone Marrow-derived Mscs and Osteogenic Differentiationmentioning
confidence: 99%